The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1093/rheumatology/ket168
|View full text |Cite
|
Sign up to set email alerts
|

Systemic sclerosis patients with and without pulmonary arterial hypertension: a nailfold capillaroscopy study

Abstract: Our results underline the relevance of early microvascular assessment in patients at risk of developing a severe complication such as PAH that can amplify the systemic microvascular impairment in SSc. More severe NVC abnormalities should lead to strict cardiopulmonary surveillance and a complete NVC study is indicated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
89
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(92 citation statements)
references
References 11 publications
2
89
0
1
Order By: Relevance
“…However, Hofstee et al [15] found it lower in SSc patients with PAH than those without it. On the other hand, Riccieri et al [16] found that the presence of avascular area was associated with PAH in SSc patients compared to those without it. Also, Ong et al [17] stated that reduced capillary density was associated with PAH and there might be a pathogenic and etiologic relationship between them.…”
Section: Discussionmentioning
confidence: 99%
“…However, Hofstee et al [15] found it lower in SSc patients with PAH than those without it. On the other hand, Riccieri et al [16] found that the presence of avascular area was associated with PAH in SSc patients compared to those without it. Also, Ong et al [17] stated that reduced capillary density was associated with PAH and there might be a pathogenic and etiologic relationship between them.…”
Section: Discussionmentioning
confidence: 99%
“…A few studies suggest that patients with PAH have systemic vascular dysfunction when compared with control subjects as determined by forearm blood flow dilation after brachial artery occlusion (15,16). A study in a small number of patients with systemic sclerosis reported that the nailfold microvasculature is significantly more affected in individuals who had PAH when compared with those who did not (17). However, no study to date has evaluated the microvasculature at the level of the sublingual mucosa in patients with PAH.…”
mentioning
confidence: 99%
“…In fact, previous studies never compared microangiopathy changes with the clinical aspect of disease, in particular DU. Moreover, no patient in our study was affected by pulmonary arterial hypertension, a possible confounding factor in analysis of results on both clinical and NVC effects [39]. Another possible limitation was the observational nature of the study, that could introduce a number of biases, e.g.…”
Section: Discussionmentioning
confidence: 94%